Protective Effects and Mechanisms of Yinchen Linggui Zhugan Decoction in HFD-Induced Nonalcoholic Fatty Liver Disease Rats Based on Network Pharmacology and Experimental Verification - Hui Jiang; Hui Jiang; Tangyou Mao; Yuyue Liu; Xiang Tan; Zhongmei Sun; Yuan Cheng; Xiao Han; Yang Zhang; Jiali Wang; Lei Shi; Yi Guo; et al. (Frontiers Media S.A., 2022)
Nonalcoholic fatty liver disease (NAFLD) is a common chronic liver disease, characterized by excessive accumulation of hepatocyte fat. However, there is no exact and effective pharmacotherapy for NAFLD. Yinchen linggui zhugan decoction (YLZD) has been widely used to treat NAFLD. Nevertheless, its pharmacological and molecular mechanisms have not been clearly elucidated. This study was carried out to investigate the active components of YLZD and explore its potential mechanisms for treating NAFLD by network pharmacology and experimental verification. The results showed that a total of 120 active components of YLZD and 365 targets were retrieved through databases, and the main active ingredients of YLZD consisted of chlorogenic acid, emodin, aloe-emodin, rhein, and geniposide. KEGG enrichment analysis revealed fundamental roles of TNF, PI3K/AKT, HIF-1α, and insulin resistance signaling pathways in the treatment of NAFLD by YLZD. Moreover, our experimental verification results showed that YLZD improved the liver pathological and cholesterol level, and reduced the expressions of TNF-α, IL-1β, IL-6, NF-κB, CCL2, and CXCL10 in NAFLD rats, which all belonged to TNF signaling pathway. The molecular docking confirmed the correlation between the four core components (chlorogenic acid, emodin, rhein, and geniposide) and key factors (TNF-α, IL-6, and NF-κB) in TNF signaling pathway. In conclusion, the present study systematically clarified the protective mechanisms of YLZD against NAFLD through targeting the TNF signaling pathway, and provided new ideas for the drug research of this disease.